2010
DOI: 10.1016/j.pio.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Slow or rapid palatal expansion for early treatment of unilateral posterior crossbite? Evaluation of the reverse chewing cycles correction

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited. In most cases authors Materials and methods:Twenty children, (9 boys, 11 girls; age, mean ± SD, 7.5 ± 1.1), 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Masticatory/chewing cycle. Concerning assessment of the masticatory cycle before and after the treatment of posterior cross-bite, seven relevant studies were identified (8-10, [21][22][23][24]. Six of the studies looked at subjects treated with expansion of the upper dental arch with the use of an appliance, and one study looked at subjects where occlusal grinding had been performed to resolve the functional unilateral posterior cross-bite.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Masticatory/chewing cycle. Concerning assessment of the masticatory cycle before and after the treatment of posterior cross-bite, seven relevant studies were identified (8-10, [21][22][23][24]. Six of the studies looked at subjects treated with expansion of the upper dental arch with the use of an appliance, and one study looked at subjects where occlusal grinding had been performed to resolve the functional unilateral posterior cross-bite.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…All of the included articles found that before treatment, there was a higher prevalence of a reverse-cycle chewing pattern in the cross-bite samples than in normal control children (8)(9)(10)24) or in the cross-bite versus the non-cross-bite side (21)(22)(23). After the completion of treatment, however, there was a normalisation of the chewing pattern in four studies (21)(22)(23)(24), whereas the remaining three studies (8)(9)(10) found that although treatment tended to lower the prevalence of the reverse-cycle chewing pattern, it did not lead to a normalisation of the patients' abnormal cycle shape (in comparison with control individuals or the non-cross-bite side). In these studies, the prevalence of the reverse-cycle chewing pattern was still apparent more often in the treated cross-bite side than in the normal control groups or the initially non-cross-bite sides of the patients.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Other diagnostic tools also have been introduced in orthodontics, such as electromyography (EMG), which is used to analyze the activity of the masticatory and facial muscles. EMG, a simple method of detecting and registering electric activity of muscle fibers, has been shown to have good reproducibility [ 17 , 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…Throckmorton et al , 2001 ;Sonnesen and Bakke, 2007 ;Piancino et al , 2006Piancino et al , , 2009Sever et al , 2010 ). This serious functional asymmetry may be prevented by orthodontic therapy at an early stage in development ( Pirttiniemi et al , 1990( Pirttiniemi et al , , 1991Lam et al , 1999 ;Nerder et al , 1999 ;Thilander and Lennartsson, 2002 ;Piancino et al , 2006Piancino et al , , 2008Piancino et al , , 2010.…”
Section: Introductionmentioning
confidence: 99%